Representações de gênero sobre o trabalho, a qualificação e as novas competências no COE - Comando de Operações Especiais da PM/SE - Lima, Susana Rezende (2013)
This research aims to examine gender representations built by professionals Special Operations Command of the Military Police of the State of Sergipe - COE, having as parameter the sexual division of labor, the value of professional qualifications and new skills, assigning special attention to the advances made by women in the organization, with respect to rights and citizenship. The approach adopted is based on the historical-critical design, with the option methodological qualitative research through case study developed in the Organization. The research population includes the effective of 98 professionals (93 men and five women) group of specialized police COE. Ten interviews were conducted semistructured with five women and five men. The Military Police is an organization that still has strong brands of conservatism in its structure, with a strict hierarchy, which has hampered over the years, access and retention of women in the workplace associated with various social representations, between which highlights the image of a physically demanding and risky activity, contact with violent situations and environments socially devalued. In the process of inclusion of women in the military police unit, to assume new positions in the hierarchy of living circles, the subject of sex workers becomes a source of status and power, leading the way in introducing and positioning jobs, a fact that sets the process of exclusion and domination within the police apparatus. The interviewees consider that there are barriers to progress more effective participation of women in the space of the Military Police, however, indicate dimensions of positive work done by them, this is because these dimensions have provided expand democratization in the corporation, as well as between the Police and society. In Special Operations Command, despite the small number of women exist, they develop functions and actions that have always been seen as suitable only for men. Education, training on gender issues for the individuals involved and included in the Corporation become important elements for changing the forms of management, organizational culture and the deconstruction of stereotypes disadvantageous for women prevailing in the organization.